In Vitro Activities of Azithromycin and Ofloxacin against Chlamydia pneumoniae in a Continuous-Infection Model - Kutlin, Andrei (American Society for Microbiology, 1999)
Chlamydia pneumoniae is a well-established cause of community-acquired pneumonia and bronchitis in adults and children. Chronic infections with C. pneumoniae have been implicated in the development of atherosclerosis and other diseases in humans. Methods currently used for the culture and propagation of C. pneumoniae are not analogous to the infection as it occurs in vivo. We have established a model of continuous C. pneumoniae infection in vitro. HEp-2 cells inoculated with CM-1 and TW-183 strains have been persistently infected for periods of over 1.5 and 2 years, respectively. The cultures were maintained without centrifugation or the addition of cycloheximide, fresh host cells, or chlamydia. We observed cycles of host cell lysis, detachment, and regrowth with both strains of C. pneumoniae. Continuous C. pneumoniae infections may more closely resemble the actual events as they occur in vivo and, therefore, may be a better model for the in vitro study of C. pneumoniae infection. When we used continuously infected cells to determine the effects of azithromycin and ofloxacin on C. pneumoniae propagation in vitro, we found that both drugs reduced but did not completely eliminate the organism. This may be an important observation, as the failure of antibiotic therapy against C. pneumoniae infection in humans has been described.